Changes in attitudes towards smoking during smoking cessation courses for Turkish- and Albanian-speaking migrants in Switzerland and its association with smoking behavior: A latent change score approach - Paz Castro, Raquel; Henninger, Mirka; Schaub, Michael P.; Salis Gross, Corina (Frontiers in Psychology, 2022)
Introduction Migrant populations usually report higher smoking rates than locals. At the same time, people with a migration background have little or no access to regular smoking cessation treatment. In the last two decades, regular smoking cessation courses were adapted to reach out to Turkish- and Albanian-speaking migrants living in Switzerland. The main aims of the current study were (1) to analyze the effects of an adapted smoking cessation course for Turkish- and Albanian-speaking migrants in Switzerland on attitudes toward smoking and smoking behavior; and (2) to elucidate whether changes in attitudes toward smoking were associated to changes in smoking behavior in the short- and in the long-term. Methods A total of 59 smoking cessation courses (Turkish: 37; Albanian: 22) with 436 participants (T: 268; A: 168) held between 2014 and 2019 were evaluated. Attitudes toward smoking and cigarettes smoked per day were assessed at baseline and 3-months follow-up. One-year follow-up calls included assessment of cigarettes smoked per day. Data were analyzed by means of structural equation modeling with latent change scores. Results Participation in an adapted smoking cessation course led to a decrease of positive attitudes toward smoking (T: β = −0.65, p < 0.001; A: β = −0.68, p < 0.001) and a decrease of cigarettes smoked per day in the short-term (T: β = −0.58, p < 0.001; A: β = −0.43, p < 0.001) with only Turkish-speaking migrants further reducing their smoking in the long-term (T: β = −0.59, p < 0.001; A: β = −0.14, p = 0.57). Greater decreases in positive attitudes were associated with greater reductions of smoking in the short-term (T: r = 0.39, p < 0.001; A: r = 0.32, p = 0.03), but not in the long-term (T: r = −0.01, p = 0.88; A: r = −0.001, p = 0.99). Conclusion The adapted smoking cessation courses fostered changes in positive attitudes toward smoking that were associated with intended behavior change in the short-term. The importance of socio-cognitive characteristics related to behavior change maintenance to further increase treatment effectiveness in the long-term is discussed.